Preparation method of polyurethane condom with antibacterial function
Through multi-layer impregnation process and precise formula design, combined with surface micro-nano structural texture and plasma surface treatment, the problems of polyurethane condoms in terms of flexibility, lubricity and comfort are solved, and comprehensive optimization is achieved in ultra-thin state, enhancing the user experience and product market competitiveness.
Patent Information
- Application Number
- CN202411789426.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyurethane condoms have problems in softness, lubricity and comfort. The surface lubricant on the material is insufficient adhesion, the friction coefficient increases, which affects the user experience, and it is difficult to achieve a balance between strength and softness in an ultra-thin state.
Through multi-layer impregnation process and precise formula design, a polyurethane condom with a gradient thickness structure was prepared. The inner layer has high cross-linking density to provide strength, and the outer layer has soft bonding and low friction characteristics optimized by softener. At the same time, the surface is etched through mold to form a micro-nano structural texture and plasma surface treatment is carried out to enhance the adhesion of the lubricant.
It realizes comprehensive optimization of mechanical properties, flexibility and comfort in ultra-thin state, reduces the friction coefficient, enhances the adhesion and durability of the lubricant, improves the user's comfort and experience, and meets the users' high demand for safety, comfort and functionality.
Smart Images

Figure CN119613777A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of condom preparation methods, and more specifically to a method for preparing a polyurethane condom with antibacterial function. Background Art
[0002] Condoms are important reproductive health products for preventing sexually transmitted diseases and achieving contraception. They are usually made of natural latex or synthetic materials. Traditional latex condoms are widely used due to their good elasticity and strength, but they also face many problems, such as latex is prone to allergies, strong odor, poor air permeability, etc. In addition, in order to meet consumers' higher demands for comfort and safety, the development of condoms is gradually moving towards multifunctionality. For example, condoms with antibacterial functions can effectively reduce the risk of infection of sexually transmitted diseases while providing contraceptive protection. Therefore, polyurethane materials with antibacterial properties and excellent biocompatibility have gradually become an ideal substitute for latex.
[0003] However, existing polyurethane condoms still have certain problems in terms of softness, lubricity and comfort. Due to the lack of lubricant adhesion on the surface of the material, the lubricant is easy to fall off during use, resulting in an increase in the friction coefficient, affecting the user experience. At the same time, it is difficult to achieve a balance between the strength and softness of the film in an ultra-thin state, which restricts the safety and comfort of the product. In addition, it is difficult to form micro-nanostructure textures on the surface with traditional processes, which further limits the improvement of condoms in terms of functionality and market competitiveness.
[0004] Therefore, in view of the above technical problems, it is necessary to provide a method for preparing a polyurethane condom with antibacterial function. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a polyurethane condom with antibacterial function to solve the above-mentioned problems.
[0006] In order to achieve the above purpose, the technical solution provided by an embodiment of the present invention is as follows:
[0007] A method for preparing a polyurethane condom with antibacterial function comprises the following steps:
[0008] S1: Preparation of polyurethane substrate: Polyester polyol and diisocyanate are polymerized, and a cross-linking agent and a chain extender are added to optimize the molecular structure to obtain a polyurethane substrate with high elasticity, high softness and biocompatibility;
[0009] S2: Adding comfort enhancer: adding composite additives including lubricant, softener, moisturizer and temperature regulator to the polyurethane base material;
[0010] S3: Film formation: A multi-layer dipping process is used to form a condom film with a gradient thickness structure through continuous coating and drying;
[0011] S4: Post-treatment: The molded condoms are subjected to plasma surface treatment to enhance the adhesion of the surface lubricant. The plasma surface treatment is performed by radio frequency plasma equipment in an inert gas environment, followed by sterilization to obtain a finished product.
[0012] As a further improvement of the present invention, the molecular weight of the polyester polyol in S1 is 1500-2500, the isocyanate is toluene diisocyanate (TDI) or diphenylmethane diisocyanate (MDI), and 0.5%-2% of a multifunctional crosslinking agent and a chain extender are added to achieve uniform crosslinking of the molecular chains.
[0013] As a further improvement of the present invention, the comfort enhancer in S2 comprises the following components and their addition amounts are calculated as a percentage of the total weight of the polyurethane substrate:
[0014] Lubricant: silicone oil, polyether silicone oil or their mixture, added in an amount of 1%-5%;
[0015] Softener: selected from citrate or phthalate compounds, added in an amount of 1%-8%;
[0016] Moisturizer: selected from sodium hyaluronate, glycerin or propylene glycol, added in an amount of 0.5%-2%;
[0017] Temperature regulator: selected from menthol or capsaicin derivatives, added in an amount of 0.1%-1%.
[0018] As a further improvement of the present invention, the film forming step in S3 adopts a double-layer or multi-layer dipping process, wherein:
[0019] The first layer of impregnation liquid is a polyurethane solution with a relatively high cross-linking density, which forms an inner layer to provide strength;
[0020] The second layer of impregnation liquid is a polyurethane solution with a higher softener content, forming a softer outer layer;
[0021] The film thickness ranges from 0.01 to 0.03 mm.
[0022] As a further improvement of the present invention, the dipping time of the multi-layer dipping process in S3 is 5-20 seconds, the drying temperature is 50-70°C, and constant temperature curing is performed after each coating, and the curing temperature is 80-100°C.
[0023] As a further improvement of the present invention, the plasma surface treatment in S4 is performed by radio frequency plasma equipment in an inert gas environment for a treatment time of 10-120 seconds to improve the adhesion and durability of the surface lubricant.
[0024] As a further improvement of the present invention, the lubricant in S4 is medical grade silicone oil or water-based lubricant, and is evenly coated on the surface of the condom through a vacuum coating process, and the amount of the lubricant is 0.5%-3% of the weight of the finished product.
[0025] As a further improvement of the present invention, the sterilization treatment in S4 adopts ethylene oxide sterilization method, and the sterilization parameters are temperature 37-55°C, gas concentration 450-600 mg / L, and sterilization time is 3-6 hours.
[0026] As a further improvement of the present invention, the polyurethane condom prepared in steps S3 and S4 has the following performance indicators: thickness of 0.01-0.03 mm; tensile strength greater than 35 MPa; elongation greater than 500%; and friction coefficient less than 0.15.
[0027] As a further improvement of the present invention, the surface of the condom in S3 is etched by a mold to form a micro-nano structure texture.
[0028] Compared with the prior art, the advantages of the present invention are:
[0029] This scheme uses a multi-layer impregnation process and precise formula design to prepare a polyurethane condom with a gradient thickness structure. The high cross-linking density of the inner layer provides excellent tensile strength and tear resistance, and the outer layer is optimized by softener to achieve soft fit and low friction properties; at the same time, the surface is etched by mold to form a micro-nano structure texture, which not only significantly reduces the friction coefficient, enhances the adhesion and durability of the lubricant, but also provides a special touch, improves the user's comfort and experience, and in addition, plasma surface treatment further optimizes the combination of the lubricant and the film surface, making the lubrication effect more lasting. This structural design achieves comprehensive optimization of mechanical properties, softness and comfort in an ultra-thin state, meets users' high demands for safety, comfort and functionality, and is suitable for industrial large-scale production, with significant market competitive advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the preparation method of the polyurethane condom of the present invention;
[0031] Figure 2 This is a schematic diagram of detection data of Example 1 of the present invention;
[0032] Figure 3 This is a schematic diagram of the detection data structure of Example 2 of the present invention;
[0033] Figure 4 This is a schematic diagram of the detection data structure of Example 3 of the present invention;
[0034] Figure 5 Schematic diagram of detection data structure according to multiple embodiments of the present invention. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] See also Figure 1-Figure 5 , a method for preparing a polyurethane condom with antibacterial function, comprising the following steps:
[0038] S1: Preparation of polyurethane substrate: Polyester polyol and diisocyanate are polymerized, and a cross-linking agent and a chain extender are added to optimize the molecular structure to obtain a polyurethane substrate with high elasticity, high softness and biocompatibility;
[0039] S2: Adding comfort enhancer: adding composite additives including lubricant, softener, moisturizer and temperature regulator to the polyurethane base material;
[0040] S3: Film formation: A multi-layer dipping process is used to form a condom film with a gradient thickness structure through continuous coating and drying;
[0041] S4: Post-treatment: The molded condoms are subjected to plasma surface treatment to enhance the adhesion of the surface lubricant. The plasma surface treatment is performed by radio frequency plasma equipment in an inert gas environment, followed by sterilization to obtain a finished product.
[0042] Among them, a polyurethane condom with a gradient thickness structure is prepared through a multi-layer impregnation process and precise formula design. The high cross-linking density of the inner layer provides excellent tensile strength and tear resistance, and the outer layer is optimized by softener to achieve soft fit and low friction characteristics; at the same time, the surface is etched by mold to form a micro-nano structure texture, which not only significantly reduces the friction coefficient, enhances the adhesion and durability of the lubricant, but also provides a special touch, improves the user's comfort and experience, in addition, plasma surface treatment further optimizes the combination of the lubricant and the film surface, making the lubrication effect more lasting. The structural design achieves comprehensive optimization of mechanical properties, softness and comfort in an ultra-thin state, meets users' high demands for safety, comfort and functionality, and is suitable for industrial large-scale production, with significant market competitive advantages.
[0043] The molecular weight of the polyester polyol in S1 is 1500-2500, the isocyanate is toluene diisocyanate (TDI) or diphenylmethane diisocyanate (MDI), and 0.5%-2% of a multifunctional crosslinking agent and a chain extender are added to achieve uniform crosslinking of the molecular chains.
[0044] Among them, in step S1, by using polyester polyols with a molecular weight of 1500-2500, TDI or MDI as isocyanate, and adding 0.5%-2% of multifunctional cross-linking agent and chain extender, the molecular structure of polyurethane can be effectively optimized and the material can be given excellent performance.
[0045] The molecular weight of polyester polyols (1500-2500) makes polyurethane have good softness and ductility while maintaining high strength and balance in mechanical properties. Too low molecular weight will lead to poor flexibility, while too high molecular weight will reduce the stability of the material.
[0046] Among isocyanates (TDI or MDI), TDI has high reactivity and is suitable for rapid reaction and industrial production, while MDI's low volatility and excellent biocompatibility are more suitable for human safety needs. The two can be flexibly selected according to needs to improve the comprehensive performance of the material.
[0047] Cross-linking agents and chain extenders (0.5%-2%); cross-linking agents such as trimethylolpropane increase the cross-linking points between molecular chains, improving the mechanical strength and wear resistance of polyurethane; chain extenders such as ethylenediamine can extend the molecular chains and improve the flexibility and elasticity of the material. Appropriate amounts of cross-linking and chain extension can also avoid the problem of excessive cross-linking causing the material to become brittle.
[0048] The above method enables the prepared polyurethane substrate to have high elasticity, high softness and excellent biocompatibility. In application, it can achieve an extremely thin thickness (0.01-0.03 mm) while maintaining high tensile strength and ductility, thereby improving wearing comfort and safety. In addition, this formula and process facilitate industrial production, reduce manufacturing costs, and ensure the stability of the product under different conditions.
[0049] The comfort enhancer in S2 includes the following components and their addition amounts are calculated as a percentage of the total weight of the polyurethane substrate:
[0050] Lubricant: silicone oil, polyether silicone oil or their mixture, added in an amount of 1%-5%;
[0051] Softener: selected from citrate or phthalate compounds, added in an amount of 1%-8%;
[0052] Moisturizer: selected from sodium hyaluronate, glycerin or propylene glycol, added in an amount of 0.5%-2%;
[0053] Temperature regulator: selected from menthol or capsaicin derivatives, added in an amount of 0.1%-1%.
[0054] Among them, in step S2, the design of the comfort enhancer can significantly improve the use experience and performance of polyurethane condoms through the optimized combination of lubricants, softeners, moisturizers and temperature regulators:
[0055] The lubricant (1%-5%) is silicone oil, polyether silicone oil or a mixture thereof, which has excellent lubricating properties, can reduce the friction coefficient of the condom surface, reduce the discomfort caused by friction during use, and enhance the durability of the product.
[0056] The softener (1%-8%) is a citrate or phthalate compound, which can effectively improve the softness of the polyurethane substrate, make the condom fit better, and enhance the comfort and natural feeling when worn.
[0057] Moisturizers (0.5%-2%) such as sodium hyaluronate, glycerin or propylene glycol can maintain the wettability of the material, prevent surface roughness caused by dryness, further improve the lubrication effect, and avoid discomfort after long-term use.
[0058] The temperature regulator (0.1%-1%) is a menthol or capsaicin derivative that provides a cool or warm feeling, thereby enhancing the comfort and interest of the condom and meeting the diverse needs of users.
[0059] The synergistic effect of lubricants and softeners makes the condom material softer and smoother, significantly reducing discomfort during use; the moisturizer further optimizes the surface properties to avoid dryness, and the addition of temperature regulators enhances user experience through the stimulation of cold and warm sensations, increasing the market competitiveness of the product. The reasonable proportion of each component ensures comfort while avoiding the impact of excessive addition on material performance or biosafety.
[0060] The film forming step in S3 adopts a double-layer or multi-layer dipping process, wherein:
[0061] The first layer of impregnation liquid is a polyurethane solution with a relatively high cross-linking density, which forms an inner layer to provide strength;
[0062] The second layer of impregnation liquid is a polyurethane solution with a higher softener content, forming a softer outer layer;
[0063] The film thickness ranges from 0.01 to 0.03 mm.
[0064] Among them, the first layer of impregnation liquid:
[0065] This layer of polyurethane solution has a high cross-linking density and forms the inner layer structure of the condom. By increasing the number of cross-linking points, the inner layer material is given higher mechanical strength and tear resistance, ensuring that the film can withstand high tensile forces without breaking during use. The high cross-linking density of the inner layer can also improve the material's wear resistance and deformation resistance, making the entire film structure more stable.
[0066] Second dip:
[0067] The content of softener in this layer of polyurethane solution is relatively high, forming a softer outer layer structure. The addition of softener improves the elasticity and smoothness of the outer layer, making the condom fit the skin better, thereby improving the comfort when wearing. Compared with the inner layer, the outer layer pays more attention to softness and touch, and has a stronger ability to combine with lubricants, further reducing friction during use.
[0068] Gradual design of film thickness (0.01-0.03 mm):
[0069] By controlling the number of coatings, dipping time and solution concentration in the multi-layer dipping process, a gradient thickness structure from the inside to the outside of the film is formed. The thinner areas enhance the softness and natural feel, while the slightly thicker areas enhance the strength, ensuring that the material has uniform mechanical properties.
[0070] The first inner layer provides the necessary mechanical strength to ensure that the film has sufficient stretch resistance and durability in an ultra-thin state; the second outer layer enhances the softness and fit through the action of softener, improving the user's comfort. The gradient thickness design realizes the functional division of the inner and outer layers. The inner layer pays more attention to durability, and the outer layer pays more attention to comfort. It not only optimizes the comprehensive performance of the film, but also makes the condom fit more naturally during use. The addition of softener in the outer layer makes the surface of the film smoother and better combines with the lubricant, further reducing the user's sense of friction during wearing and use.
[0071] The multi-layer dipping process in S3 has a dipping time of 5-20 seconds, a drying temperature of 50-70°C, and constant temperature curing after each coating, with a curing temperature of 80-100°C.
[0072] Among them, the immersion time determines the amount of polyurethane solution attached to the mold surface and the uniformity of the film thickness. If the immersion time is too short, the polyurethane solution cannot evenly cover the mold surface, which may result in insufficient film thickness or surface defects. If the immersion time is too long, excessive solution adhesion may cause the film layer to be too thick, increase the hardness of the material and affect comfort, while reducing production efficiency.
[0073] By controlling the immersion time to 5-20 seconds, a uniform film thickness (0.01-0.03 mm) can be achieved, which not only ensures the mechanical properties but also ensures the softness and conformability of the film. The drying temperature is controlled to allow the solvent to evaporate gradually to avoid shrinkage of the film or surface cracking due to excessive temperature.
[0074] If the temperature is too low (below 50°C), the solvent will evaporate slowly, which will extend the production cycle and may cause uneven film layers. If the temperature is too high (above 70°C), the polyurethane material may degrade due to high temperature, resulting in decreased film performance.
[0075] Controlling the drying temperature at 50-70°C can effectively evaporate the solvent, ensure a smooth and bubble-free film surface, and maintain the chemical stability of the polyurethane material, laying the foundation for subsequent curing steps.
[0076] If the temperature is too low (below 80°C), the cross-linking reaction will be incomplete and the mechanical properties of the film layer will be insufficient, which may lead to a decrease in tensile strength and tear resistance. If the temperature is too high (above 100°C), it may cause excessive internal stress in the material, thereby affecting the flexibility and ductility of the film.
[0077] Controlling the constant temperature curing temperature at 80-100°C can ensure the full cross-linking of the polyurethane molecular chains, improve the strength, durability and stability of the film, and avoid material embrittlement.
[0078] Reasonable coordination of immersion time and drying temperature ensures uniform thickness of each coating layer, avoiding uneven thickness or defects in the film. The constant temperature curing process makes the polyurethane molecules fully cross-linked, and the film still has excellent tensile strength, ductility and tear resistance in the ultra-thin state.
[0079] The 5-20 second dipping time and moderate drying temperature take into account both production efficiency and product quality, are suitable for industrial-scale production, and ensure product consistency and reliability. By controlling the above parameters, the final film is both soft and fit, and has sufficient strength and toughness, providing users with a safe and comfortable use experience.
[0080] The plasma surface treatment in S4 is performed by radio frequency plasma equipment in an inert gas environment for 10-120 seconds to improve surface lubricant adhesion and durability.
[0081] Among them, radio frequency plasma treatment is a technology that uses high-energy plasma to bombard the surface of materials for physical and chemical modification. In an inert gas environment (such as argon or helium), radio frequency plasma equipment excites inert gas through a high-frequency electric field to form plasma, generating a large number of active particles. These particles bombard the surface of the polyurethane film;
[0082] It can remove pollutants or weak bonding layers on the surface of the film, increase the direct contact area between the lubricant and the film, and form a micro-nano structure through physical bombardment to increase the surface roughness, thereby significantly improving the adhesion of the lubricant. The active particles stimulate the surface of the film, increase the surface energy, and improve the wetting and adhesion properties of the lubricant.
[0083] The radio frequency is usually 13.56MHz, and the electromagnetic field excites the inert gas to form a stable plasma. The inert gas (such as argon or helium) will not cause adverse chemical effects on the polyurethane film due to its chemical inertness. At the same time, its active particles have a high-energy physical bombardment effect.
[0084] Argon is often used as the inert gas source. Its active ion energy is moderate and can effectively clean and modify the film surface. Helium can also be used as an option to provide a more uniform surface treatment effect.
[0085] The treatment time is 10-120 seconds. If it is less than 10 seconds, the treatment is insufficient and the surface energy cannot be effectively improved or a stable micro-nano structure cannot be formed. If it exceeds 120 seconds, it may cause excessive bombardment of the surface, resulting in a decrease in material performance or surface damage. Controlling the treatment time within 10-120 seconds can ensure surface modification while avoiding effects on the mechanical properties of the film.
[0086] After plasma treatment, the surface energy and roughness of the film surface are significantly improved, allowing lubricants (such as silicone oil and water-based lubricants) to adhere more firmly to the film surface, avoiding the loss of lubricants during use.
[0087] At the same time, surface modification enables the lubricant to form stronger physical adhesion and chemical bonding with the film, thereby extending the retention time of the lubrication effect and significantly improving the user experience. At the same time, the use of an inert gas environment will not introduce chemical impurities, maintain the chemical stability and biocompatibility of the polyurethane film, and ensure the safety of condom materials.
[0088] The lubricant in S4 is medical grade silicone oil or water-based lubricant, and is evenly coated on the surface of the condom through a vacuum coating process. The amount of lubricant used is 0.5%-3% of the weight of the finished product.
[0089] Among them, the coating of lubricant is to reduce the friction coefficient of the condom surface and improve the smoothness and comfort during use. The vacuum coating process evenly distributes the lubricant on the surface of the film under a low-pressure environment. The vacuum environment can avoid the generation of bubbles or droplets during the coating process, so that the lubricant forms a uniform covering layer on the surface of the film.
[0090] By adjusting the parameters of the vacuum coating equipment, the coating thickness of the lubricant can be precisely controlled to ensure that the amount of lubricant is within the range of 0.5%-3% of the weight of the finished product, which not only ensures the lubrication effect but also avoids excessive addition that may cause user discomfort or increased costs.
[0091] The uniform coating of lubricant significantly reduces the friction coefficient of the condom surface, reduces the friction discomfort during use and improves comfort. At the same time, medical-grade silicone oil and water-based lubricants have good durability and can maintain the lubrication effect for a long time during use, thereby improving product reliability.
[0092] Medical-grade lubricants have excellent biocompatibility and will not cause skin irritation or allergic reactions; water-based lubricants provide a gentler option suitable for sensitive users.
[0093] The vacuum coating process can accurately control the amount and uniformity of lubricants, which is suitable for industrial large-scale production, ensuring product consistency and reducing production costs.
[0094] The sterilization treatment in S4 adopts ethylene oxide sterilization method, and the sterilization parameters are temperature 37-55°C, gas concentration 450-600 mg / L, and sterilization time is 3-6 hours.
[0095] Among them, ethylene oxide sterilization is a low-temperature chemical sterilization method that uses the strong permeability and bactericidal effect of ethylene oxide gas to inactivate microorganisms. Ethylene oxide reacts with active groups in microbial proteins and DNA to destroy their metabolic functions and genetic mechanisms, thereby achieving a sterilization effect. It is suitable for materials that cannot withstand high temperature and high humidity environments, such as polyurethane films used in condoms.
[0096] The sterilization temperature only needs to be 37-55°C, which effectively avoids the damage of high temperature to the performance of polyurethane materials (such as flexibility and strength), and the ethylene oxide gas can penetrate into every corner of the product, including the microporous structure of the film, ensuring comprehensive and thorough sterilization.
[0097] The sterilization process includes cleaning and drying the condoms to ensure that there is no excess moisture or impurities on the surface to improve the sterilization effect, placing the product in a closed sterilization chamber, injecting ethylene oxide gas, and adjusting the temperature, gas concentration and pressure while maintaining the set time. After sterilization is completed, the product is placed in a ventilated environment for degassing to ensure that the residual ethylene oxide meets safety standards (usually less than 10ppm).
[0098] The polyurethane condom prepared in steps S3 and S4 has the following performance indicators: thickness of 0.01-0.03 mm; tensile strength greater than 35 MPa; elongation greater than 500%; and friction coefficient less than 0.15.
[0099] Among them, the polyurethane condoms prepared through steps S3 and S4 have excellent performance indicators, including a thickness of 0.01-0.03 mm, a tensile strength greater than 35 MPa, an elongation greater than 500%, and a friction coefficient less than 0.15.
[0100] The ultra-thin thickness is precisely controlled through a multi-layer impregnation process, which ensures high sensitivity and improves wearing comfort; the high tensile strength is due to the high cross-linking density polyurethane solution in the inner layer, which enables the product to still have excellent tear resistance in an ultra-thin state; the elongation rate exceeds 500% through the optimization of the outer layer softener and the molecular chain extension design, ensuring that the film is not easy to break under extreme tensile conditions; the low friction coefficient is achieved by vacuum coating medical silicone oil or water-based lubricant, combined with plasma surface treatment technology, which effectively reduces friction during use and improves smoothness and comfort.
[0101] This process ensures the safety, durability and user experience of condoms, and is suitable for large-scale industrial production, with significant market competitive advantages.
[0102] The surface of the condom in S3 is etched by a mold to form a micro-nano structure texture.
[0103] The mold surface is precisely etched to form a special texture structure at the micron or nano level. During the film forming process, the polyurethane material replicates the texture of the mold surface and transfers the micro-nano structure directly to the surface of the condom film.
[0104] The micro-nano structure forms microscopic air gaps on the surface, reducing the contact area, further reducing the friction coefficient, and enhancing smoothness during use. At the same time, the texture structure provides more attachment points, significantly improving the stability and durability of the lubricant. The surface texture can also provide a special touch, increasing product diversity and market appeal.
[0105] The micro-nano structure texture formed by mold etching not only optimizes the physical properties of the condom, but also improves its comfort and functionality, giving the product higher market competitiveness.
[0106] Under standard process conditions, the process parameters are:
[0107] In the preparation of Example 1, a polyurethane substrate with high elasticity and biocompatibility was first prepared by reacting polyester polyol (molecular weight 2000) with MDI isocyanate, and adding 1% of a cross-linking agent and 1% of a chain extender; then 3% of silicone oil as a lubricant, 5% of a citrate softener, 1% of a sodium hyaluronate moisturizer and 0.5% of a menthol temperature regulator were added to the substrate to optimize the comfort and expressiveness of the material.
[0108] In the film-forming step, a double-layer dipping process is adopted, the inner layer uses a high cross-linking density polyurethane solution to enhance strength, and the outer layer adds a high softener concentration to form a soft and conformable gradient thickness film (0.01-0.03 mm), and the film is formed by 10 seconds of dipping, 60°C drying and 90°C constant temperature curing. In the post-processing stage, the adhesion of the surface lubricant is improved by 60 seconds of radio frequency plasma treatment under an argon environment, and then a 2% medical-grade silicone lubricant is applied by a vacuum coating process, and finally the sterilization is completed by ethylene oxide sterilization (45°C, 500mg / L gas concentration, 4 hours sterilization time). The final condom film has excellent mechanical properties (tensile strength greater than 35MPa, elongation greater than 500%) and surface lubricity (friction coefficient less than 0.15), and has an extremely thin thickness and good comfort, suitable for industrial production.
[0109] Embodiment 2:
[0110] Under high flexibility design, the process parameters are:
[0111] In this process, a high-strength and highly flexible polyurethane substrate is prepared by reacting a polyester polyol with a molecular weight of 2500 with TDI, and adding 0.5% of a crosslinker and 1.5% of a chain extender. On this basis, 4% of polyether silicone oil is added as a lubricant, 8% of a phthalate softener, 1.5% of glycerin is added as a moisturizer, and 0.1% of a capsaicin derivative is added as a temperature regulator to further enhance the comfort and functionality of the material.
[0112] In the film-forming stage, a multi-layer impregnation process with a 15-second impregnation time, a drying temperature of 55°C, and a constant temperature curing temperature of 85°C is used to form a strong structure with a high cross-linking density in the inner layer, and the outer layer is made more flexible by adjusting the softener content, forming a film with a gradient thickness (0.012-0.03 mm). Subsequently, a 90-second plasma surface treatment is carried out in an argon and helium mixed environment to enhance the adhesion of the lubricant, and a 3% water-based lubricant is evenly applied using a vacuum coating process. Finally, the product is sterilized by an ethylene oxide sterilization method at a temperature of 40°C, a gas concentration of 450mg / L, and a sterilization time of 3 hours to ensure the safety and stability of the product.
[0113] Embodiment 3:
[0114] Under high-strength design, the process parameters are:
[0115] In this process, polyester polyol with a molecular weight of 1500 is reacted with MDI, and 2% of a crosslinking agent and 0.5% of a chain extender are added to prepare a polyurethane substrate with high crosslinking density and excellent mechanical strength. On this basis, 2% of a silicone oil-polyether silicone oil mixed lubricant, 3% of a citric acid ester softener, 0.5% of a sodium hyaluronate moisturizer, and 0.3% of menthol are added as a temperature regulator to further optimize comfort and functionality.
[0116] In the film-forming stage, a multi-layer impregnation process with a 10-second impregnation time, a 65°C drying temperature, and a 95°C constant temperature curing temperature is used to give the inner layer an extremely high crosslinking density to enhance strength, and a small amount of softener is added to the outer layer to enhance softness, forming a film of gradient thickness (0.01-0.025 mm). Subsequently, a 120-second plasma surface treatment is performed in an argon environment to enhance the adhesion of the lubricant, and then 1% medical-grade silicone oil is evenly applied through a vacuum coating process. Finally, an ethylene oxide sterilization process with a temperature of 50°C and a gas concentration of 600mg / L is used for a sterilization time of 6 hours to ensure the sterility and safety of the product while maintaining the stability of the material.
[0117] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0118] In addition, it should be understood that although the present specification is described according to embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that those skilled in the art can understand.
Claims
1. A method for preparing a polyurethane condom with antibacterial function, characterized in that: The following steps are involved: S1: Preparation of polyurethane substrate: Polyester polyol and diisocyanate are polymerized, and a cross-linking agent and a chain extender are added to optimize the molecular structure to obtain a polyurethane substrate with high elasticity, high softness and biocompatibility; S2: Adding comfort enhancer: adding composite additives including lubricant, softener, moisturizer and temperature regulator to the polyurethane base material; S3: Film formation: A multi-layer dipping process is used to form a condom film with a gradient thickness structure through continuous coating and drying; S4: Post-treatment: The molded condoms are subjected to plasma surface treatment to enhance the adhesion of the surface lubricant. The plasma surface treatment is performed by radio frequency plasma equipment in an inert gas environment, followed by sterilization to obtain a finished product.
2. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The molecular weight of the polyester polyol in S1 is 1500-2500, the isocyanate is toluene diisocyanate (TDI) or diphenylmethane diisocyanate (MDI), and 0.5%-2% of a multifunctional crosslinking agent and a chain extender are added to achieve uniform crosslinking of the molecular chains.
3. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The comfort enhancer in S2 includes the following components and their addition amounts are calculated as a percentage of the total weight of the polyurethane substrate: Lubricant: silicone oil, polyether silicone oil or their mixture, added in an amount of 1%-5%; Softener: selected from citrate or phthalate compounds, added in an amount of 1%-8%; Moisturizer: selected from sodium hyaluronate, glycerin or propylene glycol, added in an amount of 0.5%-2%; Temperature regulator: selected from menthol or capsaicin derivatives, added in an amount of 0.1%-1%.
4. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The film forming step in S3 adopts a double-layer or multi-layer dipping process, wherein: The first layer of impregnation liquid is a polyurethane solution with a relatively high cross-linking density, which forms an inner layer to provide strength; The second layer of impregnation liquid is a polyurethane solution with a higher softener content, forming a softer outer layer; The film thickness ranges from 0.01 to 0.03 mm.
5. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The multi-layer dipping process in S3 has an dipping time of 5-20 seconds, a drying temperature of 50-70°C, and constant temperature curing is performed after each coating, with a curing temperature of 80-100°C.
6. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The plasma surface treatment in S4 is performed by radio frequency plasma equipment in an inert gas environment for 10-120 seconds to improve the adhesion and durability of the surface lubricant.
7. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The lubricant in S4 is medical grade silicone oil or water-based lubricant, and is evenly coated on the surface of the condom through a vacuum coating process. The amount of lubricant used is 0.5%-3% of the weight of the finished product.
8. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The sterilization treatment in S4 adopts ethylene oxide sterilization method, and the sterilization parameters are temperature 37-55° C., gas concentration 450-600 mg / L, and sterilization time is 3-6 hours.
9. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The polyurethane condom prepared in steps S3 and S4 has the following performance indicators: thickness of 0.01-0.03 mm; tensile strength greater than 35 MPa; elongation greater than 500%; and friction coefficient less than 0.
15.
10. The method for preparing a polyurethane condom with antibacterial function according to claim 1, characterized in that: The surface of the condom in S3 is etched by a mold to form a micro-nano structure texture.